Exploring the use of strategic influencer leadership (SIL) in health communication: a cross-cultural, multi–case study - Wolf, Katharina; Archer, Catherine; Assegaff, Syafiq; Nalloor, Joseph (Emerald, 2025)
Access to health care information is a basic human right. Influencers can help make health messaging more effective, but a focus on social media metrics may weaken their impact. Drawing on insights from three different, previously largely under-explored cultural contexts, we propose a return to the traditional understanding of strategic influence and introduce the concept of Strategic Influencer Leadership (SIL), an approach that prioritises credibility, cultural relevance and trust to ensure equitable access to vital health information.